2021
DOI: 10.3389/fnut.2021.620696
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Muscle Quantity and Quality and Fat Distribution in Diffuse Large B-Cell Lymphoma Patients

Abstract: Baseline CT scans of 116 patients (48% female, median 64 years) with diffuse large B-cell lymphoma (DLBCL) were retrospectively reviewed to investigate the prognostic role of sarcopenia and fat compartment distributions on overall survival (OS), progression-free survival (PFS), and early therapy termination. Skeletal muscle index (SMI), skeletal muscle density (SMD), and intermuscular adipose tissue (IMAT) were quantified at the level of the third lumbar vertebra (L3) and proximal thigh (PT). Low L3-SMD, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In Besutti's study, no significant difference was observed between different the BMI groups (<25, 25-30, ≥30) in terms of OS and PFS. However, sarcopenia in patients with obesity have the worst survival after further stratifying patients into sarcopenia and obesity group (18). As a result, the prognostic value of sarcopenia in DLBCL cancer patients with obesity, normal weight, and underweight should be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Besutti's study, no significant difference was observed between different the BMI groups (<25, 25-30, ≥30) in terms of OS and PFS. However, sarcopenia in patients with obesity have the worst survival after further stratifying patients into sarcopenia and obesity group (18). As a result, the prognostic value of sarcopenia in DLBCL cancer patients with obesity, normal weight, and underweight should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were retrospective cohort studies. The 12 included studies included 2,324 participants, among whom 996 were diagnosed with sarcopenia (18,19). Seven studies used SMI at the third lumbar vertebra level (L3) on computed tomography (CT) (CT-L3-SMI) for the measurement of skeletal muscle mass (18)(19)(20)(21)(22)(23)(24).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenia is associated with shorter survival, reduced response to treatment, increased treatment‐related toxicities, frequent dose reduction, and early termination of treatment. 13 , 24 , 25 , 26 , 27 Hypoalbuminaemia is a predictive factor for shorter survival, decreased relative dose intensity of anthracycline and cyclophosphamide, and increased risk of TRM. 28 , 29 , 30 , 31 , 32 High NLR is also correlated with shorter survival, lower CR rate, advanced stage, higher LDH level, and increased risk of depression.…”
Section: Discussionmentioning
confidence: 99%